2022
DOI: 10.3390/rs14174296
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Climate Change, Vegetation Growth, and Elevated Atmospheric CO2 Concentration to Variation in Water Use Efficiency in Subtropical China

Abstract: Ecosystem water use efficiency (WUE) plays an important role in maintaining the carbon assimilation–water transpiration balance in ecosystems. However, spatiotemporal changes in WUE in the subtropical region of China (STC) and the impact of driving forces remain unclear. In this study, we analyzed the spatiotemporal variation in WUE in the STC and used ridge regression combined with path analysis to identify direct and indirect effects of climate change, vegetation growth, and elevated atmospheric CO2 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…From the measurement results, the 10 plots have different canopy structures. Xiao et al (2022) explained that the condition of crown cover can be beneficial for the growth of certain species in the vegetation community (tolerant species) and detrimental to other species (intolerant species). Canopy closure also affects the microclimate changes in plants.…”
Section: Environmental Parametersmentioning
confidence: 99%
“…From the measurement results, the 10 plots have different canopy structures. Xiao et al (2022) explained that the condition of crown cover can be beneficial for the growth of certain species in the vegetation community (tolerant species) and detrimental to other species (intolerant species). Canopy closure also affects the microclimate changes in plants.…”
Section: Environmental Parametersmentioning
confidence: 99%
“…Jasechko et al made water resource predictions indicating that improvements in the simulation of biological flux should be prioritized in the development of climate models [26]. Li et al showed that LAI was the major factor driving changes in WUE [17]; other important factors affecting changes in WUE included the atmospheric CO 2 concentration and VPD [27]. Wei et al found that soil moisture was a key factor affecting changes in EPE [23].…”
Section: Introductionmentioning
confidence: 99%
“…The Leaf Area Index (LAI) is a crucial biophysical parameter of vegetation [2]. It is an essential input parameter for vegetation dynamics, phenology monitoring, crop yield estimation, and climate model [3][4][5][6], and LAI can also detect changes in climate and land use/cover [6,7].…”
Section: Introductionmentioning
confidence: 99%